New laws that prohibit conversion therapy pose no material risk to evidence-based and clinically appropriate practice. (June 2022) - Ryan, Christopher J; Callaghan, Sascha
Objective: To examine the extent to which the Sexuality and Gender Identity Conversion Practices Act 2020 (ACT) and Change or Suppression (Conversion) Practices Prohibition Act 2021 (Vic) might pose a risk to evidence-based and clinically appropriate practice. Method: Using a recent publication by Parkinson and Morris as a starting point, the provisions of the new legislation are carefully examined. Results: The ACT and Victorian laws do not imperil psychiatrists undertaking evidence-based and clinically appropriate practice. Conclusions: While it may be wise for psychiatrists to abandon this area of practice if they hold strong personal beliefs that the failure to identify with one's natal gender is morally wrong, nothing in the new laws should deter psychiatrists from providing people with gender dysphoria with evidence-based and clinically appropriate care.